A systematic virtual reality-based approach to support the professional development of teachers - Stavroulia, Kalliopi Evangelia; Lanitis, Andreas (My University, 2018)
The purpose of this paper is to present a virtual reality (VR)-based approach to teacher in-class training that will allow teachers to experience an entirely new way of training. The proposed virtual reality tool aims to provide strong support for teachers’ professional development through dedicated applications that address real training needs. The overall concept of the VR tool is to address specific teachers’ competences, defined based on an extensive documentation of existing teachers’ competence models and significant guidance by experts. The implementation of the VR application followed a full design cycle, a five-phase process like that of the ADDIE model, targeting mainly the cultivation of empathy and reflection skills among the users. After conducting several experiments with in-service and pre-service teachers, promising results regarding the cultivation of empathy and reflection skills were observed.
Keywords: Virtual reality; Teachers; Teacher training; Empathy; Reflection